2015
DOI: 10.1097/jtn.0000000000000165
|View full text |Cite
|
Sign up to set email alerts
|

Defining Leadership in a Changing Time

Abstract: The purpose of this article is to discuss the difference between leadership and management. Leadership and management have been discussed for many years. Both are important to achieve success in health care, but what does that really mean? Strong leaders possess qualities that inspire others to follow them. This fosters team engagement, goal achievement, and ultimately drives outcomes. Managers plan, organize, and coordinate. It takes dedication, motivation, and passion to be more than a manager and be a good … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…1. Fall 2020 32 leadership styles that have been identified as well as factors that influence leadership, including but not limited to, resources, setting, and personality (Elwell & Elikofer 2015). Leaders tend to have a clear vision.…”
Section: Leadership In Higher Educationmentioning
confidence: 99%
“…1. Fall 2020 32 leadership styles that have been identified as well as factors that influence leadership, including but not limited to, resources, setting, and personality (Elwell & Elikofer 2015). Leaders tend to have a clear vision.…”
Section: Leadership In Higher Educationmentioning
confidence: 99%
“…While Mianda et al focused on nurses, these findings can be reasonably extrapolated into the EMS space given the relatability in their findings, similar findings of international literature and the lack of South African EMS specific research [8] , [9] , [10] . This is very concerning given how fundamental effective leadership is to promoting and sustaining good quality patient care and supporting a healthy, safe clinical working environment [8 , 11 , 12] .…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, professionalism can be viewed as the outward facing, tangible manifestation of an organisations work ethic, embedded within the organisational culture, and cultivated by the activities of the leadership (and leaders) within the given organisation [9 , 11 , 13 , 14] . Within the EMS setting, research has shown that paramedics will role model other paramedics that are respected and recognised for living the values and beliefs that are positively regarded within the given work systems, and that these role models will be sought after within the shared working environment [1 , 9 , 10 , 12 , 14 , 15] . Understanding the relationship between leadership, role modelling and professionalism is key to understanding the rationale behind the value and importance of a ‘ System of Caring’ in connecting the various stakeholders within an EMS work system, to a shared set of values and beliefs that will then drive the work ethic, which is experienced as professionalism and measured as good quality care and a safe clinical working environment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This may imply that a leader should enhance all the relevant aspects of the organisation, which includes the personnel. Furthermore, leadership is not a novel idea, it has been researched extensively and has been found to direct workgroups, initiate improvements in the functioning and performance of organisations, and subsequently help organisations achieve their goals (Elwell & Elikofer, 2015;Saleem & Naveed, 2017). Common sense dictates that the organisation is not merely a lifeless and mechanical construct.…”
Section: Introductionmentioning
confidence: 99%